Helicobacter pylori Infection in Persons with Intellectual Disability in Residential Care in Israel - Joav Merrick; Shoshana Aspler; Inessa Dubman (The Scientific World Journal)
Helicobacter pylori (formerly Campylobacter pylori) was identified in 1982 by researchers from Australia as a pathogenic factor in peptic ulcer disease. Due to the few studies on H. pylori infection conducted in the population of persons with intellectual disability it was decided to conduct a clinical study in Israel. The purpose of the study was to determine the occurrence of H. pylori infection in persons who presented with severe dyspeptic symptoms and to monitor clinically the effect of treatment. The Division for Mental Retardation in Israel provides service to 6,022 persons in 53 residential care centers and 1 in central Israel was selected for this pilot study. The study has been performed since 1999 and each patient who came to the medical clinic of the institution with severe dyspeptic symptoms was examined clinically and a blood specimen drawn for IgG antibodies to H. pylori (ELISA, Pharmatop Millenia). In case of positive serology, triple drug treatment (amoxycillin, metronidazole, and pantoprazole or omepra-zole) was initiated for 1 week. Since 1999 a total of 43 persons (total population in care was 224) had severe dyspeptic symptoms and 42 persons (98%, 26 males, 16 females, mean age 45 years, mean institutionalization 20 years) had Helicobacter infection. All patients were treated for 1 week, but six patients received an extra month of omeprazole due to persistent symptoms. At follow-up, clinically all patients had improvement and only seven still had minor complaints (83% treatment success). Persons with developmental disability, intellectual disability, or mental retardation in residential care presenting with severe dyspeptic symptoms had a high incidence of H. pylori infection. Therefore, we recommend serology or urea breath investigations in this population presenting with dyspeptic symptoms and triple drug treatment for 1 week in case of positive findings.